2020
DOI: 10.1002/anie.202013017
|View full text |Cite
|
Sign up to set email alerts
|

Safe, Scalable, Inexpensive, and Mild Nickel‐Catalyzed Migita‐Like C−S Cross‐Couplings in Recyclable Water

Abstract: A new approach to C−S couplings is reported that relies on nickel catalysis under mild conditions, enabled by micellar catalysis in recyclable water as the reaction medium. The protocol tolerates a wide range of heteroaromatic halides and thiols, including alkyl and heteroaryl thiols, leading to a variety of thioethers in good isolated yields. The method is scalable, results in low residual metal in the products, and is applicable to syntheses of targets in the pharmaceutical area. The procedure also features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…Our previous reports, [19][20][21][22] as well as the work of others, [23][24][25][26][27] showed that micellar photocatalysis is an attractive tool for the activation of stable chemical bonds under mild reaction conditions. It can improve selectivity of processes and prolong the lifetimes of highly energetic intermediates by pre-organizing the components in the reaction mixture.…”
Section: Introductionmentioning
confidence: 95%
“…Our previous reports, [19][20][21][22] as well as the work of others, [23][24][25][26][27] showed that micellar photocatalysis is an attractive tool for the activation of stable chemical bonds under mild reaction conditions. It can improve selectivity of processes and prolong the lifetimes of highly energetic intermediates by pre-organizing the components in the reaction mixture.…”
Section: Introductionmentioning
confidence: 95%
“…32 A sustainable method for C-S bond formation was developed by Lipshutz and co-workers by employing an inexpensive micellar catalyst system in water (Scheme 13). 53 It consisted of Ni(Phen)2Br2, Zn powder, base (K3PO4, Cs2CO3 or KO t Bu) in a 2 wt% TPGS-750-M (α-tocopherol-methoxypoly-ethylenglycolsuccinate) aqueous solution. Aryl iodides and bromides were coupled with aryl as well as alkyl thiols using relatively low catalyst loading (0.7-1.4 mol%).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Scheme 13 Ni-based micellar catalysis for the C-S bond formation. 53 A mechanistically different type of catalyst for an efficient coupling of aryl bromides and iodides was employed by the group of Paul (Scheme 14). 54 The tetradentate singlet diradical Ni(II) complex Ni3 with two non-innocent ligands enabled coupling of a broad range of compounds, however chlorides reacted with lower yield.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[17,18] We wished to achieve target reactivity through initial C-Cl activation followed by intramolecular 1,5 hydrogen-atom transfer (1,5-HAT). [19] Our previous reports, [29][30][31] as well as the work of others, [32][33][34][35][36] showed that micellar photocatalysis is an attractive tool for the activation of stable organic halides. It enables pre-organization of the components in the reaction mixture and provides high hydration energy of the released halide anions.…”
Section: Introductionmentioning
confidence: 96%